Primary-Secondary Wavelength Spectrophotometric Determination of Trace Amounts of Cadmium in Wastewater with New Chromogenic Agent m-Nitrobenzenediazoameno azobenzene - Gao, Hong-Wen; Tao, Mei; Chen, Yun-Sheng; Zhang, Peng-Fei (Asian Journal of Chemistry, 2010)
In basic solution and in the presence of non-ionic surfactant emulsifier OP, cadmium (Cd2+) reacts with new chromogenic agent, m-nitrobenzenediazoaminoazobenzene (m-NBDA) to form yellow complex. This paper describes the determination of trace amounts of cadmium in wastewater by the updated method named primary-secondary wavelengths spectrophotometry (PSWS). The results showed that the working wavelengths should be selected at 460 and 550 nm and such a method gives higher precision, accuracy and sensitivity than that of ordinary spectrophotometry. By testing several wastewater samples, the relative standard deviations were less than 9% and the recovery rate of Cd between 91.8 and 110%.